Diabetic regulation of subjects with type 2 diabetes mellitus is associated with serum vitamin D levels - Erkus,Edip (2019)
SUMMARY OBJECTIVE Vitamin D deficiency is not only associated with bone metabolism but also with diabetes mellitus. We aimed to study the possible association between serum vitamin D concentration and HbA1c level in patients with type 2 diabetes mellitus (T2DM) in this retrospective report. METHODS Patients with T2DM were enrolled to the study either in regulated or non-regulated T2DM groups, according to HbA1c levels. An HbA1c level of <8% was considered as relatively controlled and others were considered as poorly controlled T2DM. RESULTS Serum vitamin D levels in poorly controlled T2DM subjects (9.4 (4.9-34) ng/ml) were significantly lower than that of the relatively well regulated T2DM patients (13.5 (3.4-36) ng/ml) (p=0.03). Vitamin D was strongly and inversely correlated with HbA1c levels (r= -0.295, p=0.005). CONCLUSION Whatever the cause or result of the diabetes mellitus, it is clear that lower vitamin D is strongly associated with worse diabetic regulation in T2DM subjects. Randomized controlled larger studies, which research the relation between diabetic regulation and vitamin D status, are needed to claim whether it could be a therapeutic target in future in diabetic subjects.